Synthesis of 2-hydroxy-5-(1-(2-(pyrazine-2-carbonyl) hydrazono) hexyl) benzoic acid, a pyrazinamide analog of salicylic acid - Alea, Glenn V. (Animo Repository, 2013)
The occurrence of resistant strains of Mycobacterium tuberculosis has driven current research on combining current anti-tuberculosis drugs and other bioactive molecules to enhance their efficacy against susceptible and resistant strains of the bacteria. In this study, a salicylic acid derivative of pyrazinamide, 2-hydroxy-5-(1-(2-(pyrazine-2-carbonyl) hydrazono) hexyl) benzoic acid was synthesized and characterized. The compound was prepared by coupling a pyrazinamide moiety, one of the first line drugs used to treat tuberculosis and a salicylic acid derivative with a 6-carbon alkyl chain. The salicylic acid derivative was generated via Friedel-Crafts acylation of methyl salicylate followed by base hydrolysis of the acylated product. This was coupled with the pyrazinamide moiety via imine formation. The product, 2-hydroxy-5-(1-(2-(pyrazine-2-carbonyl) hydrazono) hexyl) benzoic acid was obtained as an off-white powder in 62% yield.